Does education increase ethical sensitivity a semi-experimental study - Şerife Yılmaz; Gamze Özbek Güven (Scientific Reports)
Abstract Ethics education plays a crucial role in enhancing the ethical sensitivity of nursing students. This study aimed to assess the impact of an ethics course on the ethical sensitivity levels of nursing students. In this study, one-group pretest-posttest semi-experimental design method is used. The mean total score of the Ethics Sensitivity Scale for Nursing Students before education was determined as 4.93 (neutral), while the mean score increased to 5.62 (significant) after education. There was a statistically significant difference between the pre-education and post-education mean scores of students who reported encountering ethical problems during clinical practice. The findings underscore the importance of ethics education in fostering the ethical sensitivity and awareness of nursing students. They also highlight the need for high-quality ethics education that integrates theoretical knowledge with engaging content, real-life case studies, and practical applications to enhance students’ learning experiences.